2023
DOI: 10.1126/sciadv.adg7135
|View full text |Cite
|
Sign up to set email alerts
|

Does vegetation accelerate coastal dune erosion during extreme events?

Abstract: A broadly accepted paradigm is that vegetation reduces coastal dune erosion. However, we show that during an extreme storm event, vegetation surprisingly accelerates erosion. In 104-m-long beach-dune profile experiments conducted within a flume, we discovered that while vegetation initially creates a physical barrier to wave energy, it also (i) decreases wave run-up, which creates discontinuities in erosion and accretion patterns across the dune slope, (ii) increases water penetration into the sediment bed, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 33 publications
0
8
1
Order By: Relevance
“…Hinsdale Wave Research Laboratory, Oregon State University, Corvallis, OR, USA, to obtain simultaneous measurements of wave forcing, currents, sediment transport, and morphodynamics. A pre‐storm beach profile from Mantoloking, New Jersey, USA, typical of many sandy beaches (Luijendijk et al., 2018) was simulated (Feagin et al., 2023). The beach profile was constructed after applying scaling laws (Equations 1 and 2, Van Rijn et al., 2011) using natural sand sourced from South Beach in Newport, Oregon.…”
Section: Methodsmentioning
confidence: 99%
“…Hinsdale Wave Research Laboratory, Oregon State University, Corvallis, OR, USA, to obtain simultaneous measurements of wave forcing, currents, sediment transport, and morphodynamics. A pre‐storm beach profile from Mantoloking, New Jersey, USA, typical of many sandy beaches (Luijendijk et al., 2018) was simulated (Feagin et al., 2023). The beach profile was constructed after applying scaling laws (Equations 1 and 2, Van Rijn et al., 2011) using natural sand sourced from South Beach in Newport, Oregon.…”
Section: Methodsmentioning
confidence: 99%
“…Examples of process controls include an increase in wave energy, a change in the angle of wave approach (van Bemmelen et al., 2020), or elevated water levels (Sherman & Nordstrom, 1985). Examples of structural controls include beach nourishments (van Bemmelen et al., 2020), frozen beaches, vehicle tracks (Sherman & Nordstrom, 1985), or vegetation (Feagin et al., 2023). Structural controls like the transition from beach to foredune in the beach profile may also cause scarp formation when exposed to energetic wave conditions.…”
Section: Introductionmentioning
confidence: 99%
“…That is, depending on dune morphology and winter conditions, large dunes can erode more substantially than smaller dunes (van Puijenbroek, Nolet, et al, 2017), which we found in our experiment. While vegetation is generally found to reduce erosion in winter, the extent to which this happens depends on the morphological characteristics of the species and environmental conditions (e.g., wind and wave conditions) (Feagin et al, 2023;Innocenti et al, 2021;Maximiliano-Cordova et al, 2019). Since sand couch has a relatively dispersed shoot organization and short shoots, it is less effective at reducing erosion than, for example, marram grass (van Puijenbroek, Nolet, et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…While in general vegetation is expected to reduce erosion, it has recently been found that in extreme storm conditions vegetation can increase erosion (Feagin et al, 2023). Moreover, I found that larger dunes formed by sand couch eroded more than smaller dunes in winter (Chapter 4).…”
Section: Effects Of Global Change On Early Dune Developmentmentioning
confidence: 96%
See 1 more Smart Citation